CORPORATE SOCIAL PERFORMANCE AND FINANCIAL STABILITY: EVIDENCE FROM ISLAMIC, SOCIAL AND CONVENTIONAL BANKING MODELS - Mohamed Sultan, Syed Alwi Bin; Wan Ahmad, Wan Marhaini Binti; Ismath Bacha, Obiyathulla; Ramlee, Roslily (Bank Indonesia, 2024)
This paper addresses two key issues in Corporate Social Performance (CSP) research. First, it investigates the impact of CSP on Financial Stability (FS), and second, it examines the influence of different banking models on the relationship between CSP and FS. Using a cross-country sample of 117 financial institutions from 36 countries over an 8-year period (2013-2020) and the System Generalized Method of Moments (GMM) estimation method, it finds that banking models significantly affect the CSP-FS relationship. This is attributed to diminishing marginal benefits of economic growth beyond a certain level of financial intermediation, which increases financial risk. The results give new insights into the synergies and divergences between different banking models and the overarching goals of social performance and financial stability. This research contributes novel insights that can inform policymakers, regulators, and industry stakeholders in their quest for a more resilient and sustainable banking sector.